Higgs decay rate to two photons in a model with two fermiophobic-Higgs doublets - Cárdenas, H.; Machado, A. C B; Pleitez, V. [UNESP]; Rodriguez, J.-Alexis (American Physical Society (APS), 2013)
We consider a three Higgs doublet model with an S3 symmetry in which beside the standard model-like doublet, there are two fermiophobic doublets. Due to the new charged scalars, there is an enhancement in the two-photon decay, while the other channels have the same decay widths as the standard model neutral Higgs. The fermiophobic scalars are mass degenerated unless soft terms breaking the S3 symmetry are added. © 2013 American Physical Society.